## Trending News

Promoted

### 1 Answer

Relevance

- llafferLv 71 month ago
This is like your previous questions, and probably easier than before. Are you actually learning from these or are we just doing your homework?

f(x) = x² + 7x and g(x) = 5/x

g(f(t)) means the output of f(t) is the input into g(x) so we need an expression for f(t), first. Just substitute t for x and that's it:

f(x) = x² + 7x

f(t) = t² + 7t

Now use this as the input into g(x):

g(x) = 5/x

g(t² + 7t) = 5 / (t² + 7t)

That's it. Nothing else to simplify, here.

Still have questions? Get your answers by asking now.